Genetic studies on the role of the nucleoside transport function in nucleoside efflux, the inosine cycle, and purine biosynthesis. - Ullman, B (1983)
A mutant clone (AU-100) which is 90% deficient in adenylosuccinate synthetase activity was characterized from wild-type murine S49 T-lymphoma cells. This AU-100 cell line and its hypoxanthine-guanine phosphoribosyltransferase-deficient derivative, AUTG-50B, overproduce purines severalfold and excrete massive amounts of inosine into the culture medium (Ullman et al., Proc. Natl. Acad. Sci. U.S.A. 79:5127-5131, 1982). We introduced a mutation into both of these cell lines which make them incapable of taking up nucleosides from the culture medium. The genetic deficiency in nucleoside transport prevents the adenylosuccinate synthetase-deficient AU-100 cells from excreting inosine. Because of an extremely efficient intracellular inosine salvage system, the nucleoside transport-deficient AU-100 cells also no longer overproduce purines. AUTG-50B cells which have been made genetically deficient in nucleoside transport still overproduce purines but excrete hypoxanthine rather than inosine. These studies demonstrate genetically that nucleoside transport and nucleoside efflux share a common component and that nucleoside transport has an important regulatory function which profoundly affects the rates of purine biosynthesis and purine salvage.